Investigating the role of scaffolds for rotator cuff repair - Smith, R (2016)
Surgical repairs of large-massive rotator cuff tendon tears often fail. Scaffolds can be used to augment tendon repair, but few scaffolds have demonstrated clinical efficacy. The aim of this thesis was to evaluate and compare several different types of commercially available scaffolds. Three important aspects of scaffold performance were studied: mechanical properties, tenocyte response, and macrophage response. In terms of mechanical properties, synthetic scaffolds had superior macroscale mechanical properties compared to biological scaffolds, but remained significantly weaker than native human supraspinatus tendon. The microscale mechanical properties of biological scaffolds were similar to those of the human supraspinatus tendon, but synthetic scaffolds were significantly stiffer on the microscale. None of the tested scaffolds mimicked the mechanical properties of human supraspinatus tendon on both the macroscale and microscale. The tenocyte study revealed that more cells initially attached to synthetic scaffolds with aligned fibres. However, over 13 days, the human biological scaffold promoted the greatest tenocyte proliferation. The non-cross-linked porcine biological scaffold stimulated the highest expression of COL1A1 and COL3A1 mRNA. Human macrophages generated a pro-inflammatory response towards the non-cross-linked porcine biological scaffold tested. The cross-linked porcine biological scaffold prompted a chronic inflammatory response, whereas the human biological and synthetic scaffolds did not induce an overt inflammatory response. This study highlights significant variation in the properties and performance of different commercially available scaffolds. It also illustrates the inadequacy of many existing scaffolds to successfully augment a surgical rotator cuff repair. Future scaffolds should be specifically designed to meet the mechanical and biological demands of the target tissue. The pipeline of in vitro tests developed in this thesis could be used to screen new scaffolds and help determine which scaffolds to evaluate in animal models and human trials.